Nexus thinking needed to implement COP15 biodiversity targets - DeClerck, Fabrice A.J.; Navarrete Frias, Carolina (CGIAR System Organization, 2023)
In December 2022, over 190 nations gathered in Montreal, Canada to finalize the Global Biodiversity Framework, an ambitious plan to save the Earth’s biodiversity. The United Nations Global Biodiversity Conference, or COP15, concluded with 23 ambitious targets ranging from land restoration and conservation to promoting sustainable consumption.